Examining Challenges that Students Face in Learning Organic Chemistry Synthesis - Issa I. Salame; Pauline Casino; Natasha Hodges (International Journal of Chemistry Education Research, 2020)
Organic chemistry is the offered after general chemistry and is the course that many find it challenging and difficult. Synthesis is first introduced in organic chemistry I course and is widely considered as one of the topics in which students struggle with and is evident in their performance in the topic. Our method of data collection is a Likert-type and open-ended questionnaire that was distributed at the end organic chemistry I course in an anonymous fashion. The collected data enabled us to examine the challenges students face in learning organic chemistry synthesis. Our findings support the notion that students have many difficulties with multistep organic chemistry synthesis including challenges recalling all of the varied required reactions, the amount of content and topics covered in organic chemistry, conceptual understanding of needed important topics such as mechanisms, acids and bases, nucleophiles and electrophiles, and stereochemistry, and problem-solving competency. Students view organic chemistry synthesis as challenging because of their reliance on memorization of a large number of reactions, reagents, and rules, poor conceptual understanding of the topics, ineffective teaching methods which lacks active learning and student engagement, and the myriad number of possible pathways to solve synthesis problems. Our participants suggest that memorization and rote-learning plays an important role in the learning of multistep organic synthesis, which might cause a hindrance to process of learning and can impede students’ problem-solving ability.